Varı-Sımplex Dıscıplıne" -Alexander Dıscıplıne - (Clınıcal Evaluatıon) - Enis Güray; Ayhan Enacar (Galenos Yayinevi, 1994)
In our study, the historical progress of "Straight-Wire" appliances as well as their general characteristics have been examined and specifically "The Alexander Discipline" has been examined within general principles such as brackets system, and arch wire sequences. 2 -extraction-cases treated by means of this technique have been presented and the comparative discussion of the caharacteristics of this mechanic has been made.